Memory Strategies in Vocabulary Learning: Evidence from Junior High School EFL Learners - Nurhafizah; Ambo Dalle; Mujahidah; Magdahalena Tjalla; Zulfah Fakhruddin (FOSTER: Journal of English Language Teaching, 2026)
This study investigates the use of memory strategies in vocabulary learning among junior high school EFL learners in an Indonesian Islamic school context. Although vocabulary memorization is commonly emphasized in classroom practice, limited attention has been given to how young learners cognitively process and retain lexical items. This study addresses this gap by examining the types and frequency of memory strategies used by students in a daily “password class” routine, where learners recall English words before entering the classroom. A quantitative descriptive design was employed involving 21 seventh-grade students. Data were collected using an adapted version of Gu’s (2018) Vocabulary Learning Questionnaire (VLQ 6.4), focusing on three categories of memory strategies: rehearsal, encoding, and activation. The data were analyzed using descriptive statistics and inferential analysis (One-Way ANOVA and Tukey HSD). The findings revealed statistically significant differences among the three strategies (p < .001), with encoding strategies showing the highest mean score (M = 3.70), followed by activation (M = 3.34), and rehearsal strategies (M = 2.89). These results indicate that learners tend to engage more in deeper cognitive processing, such as association, visualization, and contextual use, rather than relying solely on repetition. This study contributes to understanding vocabulary learning strategies among young EFL learners by emphasizing the roles of encoding and activation strategies in vocabulary learning. Pedagogically, the findings suggest that meaningful, communicative activities should complement memorization routines to enhance vocabulary retention and productive language use.